Bilateral Anophthalmia in Dog Associated with Congenital Penile Malformation - Rodrigues, Nhirneyla Marques; Landi, Ulisses Nilo; Quessada, Ana Maria; Freitas, Marcus Valerius de Matos; Pereira, Cristian Francisco de Carvalho; Silva, Jeferson da Cruz; Dantas, Sávio Soares Barbosa; Maia, Luan Tezei (Acta Scientiae Veterinariae, 2022)
Background: Anophthalmia refers to the complete absence of an eyeball. It is a very rare congenital condition that affects all breeds of dogs, which may be unilateral or bilateral. Anophthalmia results from a severe developmental deficiency in the primitive forebrain, prior to the formation of the optic sulcus. This condition has a complex etiology, and chromosomal, monogenic, and environmental causes have already been identified. There might be an association between anophthalmia and other congenital abnormalities. This case report aimed to report the case of a male dog with bilateral anophthalmia associated with penile malformation. Case: A 3-year-old male mongrel dog was evaluated in a clinical consultation at the Veterinary Medical Teaching Hospital of the Federal University of Piauí (UFPI) - Teresina - Brazil, with signs of anemia and diarrhea. His vaccinations were not up to date (multiple and anti-rabies), presented ectoparasites (ticks), and showed inappetence. The owner reported that the animal was blind from birth, was already well adapted to its environment, had the company of other animals, and had no access to the street. On clinical examination, the animal had a good body score. The eyelids were bilaterally present with normally developed eyelashes. Both the head and face had a symmetrical appearance, without structural abnormalities, and the palpebral fissures were narrow. When opening the eyelids manually, the presence of the conjunctiva was observed bilaterally, the orbits were shallow, and neither orbit contained the eyeball. Further inspection with an ophthalmic clinical flashlight did not reveal any other ocular structures. The initial diagnosis was suggestive of bilateral anophthalmia. Ultrasound examination of the ocular region confirmed the presence of bilateral anophthalmia. A general physical examination revealed a malformed penis with a persistent penile frenulum. Regarding systemic clinical signs (apathy, inappetence, diarrhea, and anemia), clinical and laboratory examinations led to the suspicion of verminosis. Discussion: The dog in this report had a good body score; however, this type of malformation can generate non-viable puppies. Anophthalmia is an extremely rare congenital ocular malformation, both in humans and companion animals, in which there are no ocular structures in the orbits, and these structures (orbits) in affected individuals are generally small and shallow, as seen in the dog in this report. Ultrasonographic examination confirmed the bilateral anophthalmic condition, being the most accurate method of diagnosing this congenital condition. The animal in this report presented with anophthalmia associated with penile malformation. This type of association until this case report has only been described in humans and mice, and is probably caused by a mutation in the Sox2 gene, which is responsible for the protein of the same name, which makes the maturation of ocular tissues in the primitive forebrain. Thus, it is likely that such congenital alterations are the cause of the malformations observed in this animal. Maternal vitamin A deficiency, a factor known to cause ocular malformations, may also be involved in the etiology of congenital diseases. Nutritional imbalances in dogs are common in the animal’s region of origin The dog in this report had a normal life. Although it is a condition that causes blindness, dogs can have a normal life and welfare, even with bilateral anophthalmia. Keywords: canine, persistence penile frenulum, eye, congenital anomalies. Título: Bilateral Anophthalmia in Dog Associated with Congenital Penile Malformation. Descritores: canino, doenças animais, genética, anomalias congênitas.